Neutron calibration field at Institute for Nuclear Science and Technology - Le , Ngoc Thiem; Nguyen , Ngoc Quynh; Ho , Quang Tuan; Trinh , Van Giap; Nguyen , Tuan Khai; Nguyen , Huu Quyet (Nuclear Science and Technology, 2016)
In this study, a neutron calibration field of a 241Am-Be standard source at the Institute for Nuclear Science and Technology is characterized in terms of neutron spectral fluxes and neutron ambient dose equivalent ( ) rates based on ISO 8529 recommended generalized fit method together with measurements using a Bonner Sphere Spectrometer and MAXED unfolding techniques. The total, direct and scattered neutron components as well as rates and neutron spectral fluxes are separated from each other. The direct rates and neutron spectral fluxes in the free field as functions of distances from the source are also theoretically calculated based on the neutron source strength. The comparison between experimental data and theoretical calculations of the rates and neutron spectral fluxes shows good agreement within 3%, this has confirmed the reliability of the field characterization process and its applicability in the practical calibration works for neutron survey meters.